2005
DOI: 10.1177/1084822305278129
|View full text |Cite
|
Sign up to set email alerts
|

From Hospital to Home and Back Again: A Study in Hospital Admissions and Deaths for Home Care Patients

Abstract: In this study, the authors examined causes of deaths or hospitalizations of adult home care patients during an 18-month period using a retrospective medical record audit. The site of the study was the home care program of a three-hospital system. Of 4,303 cases, 101 adult patients met study criteria of hospitalization or death. The death rate in the sample was 0.48%, and the hospitalization rate was 1.9%. Wound deterioration and falling accidents were principal causes for rehospitalizing patients. Increasing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
(54 reference statements)
0
8
0
2
Order By: Relevance
“…), such as problems with nutrition, risk of falls or fall‐related injuries, nausea and vomiting, bleeding especially from the stomach or intestine, dizziness, delirium, stroke and need for hospital admission (Taft et al . , Hartikainen et al . , Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), such as problems with nutrition, risk of falls or fall‐related injuries, nausea and vomiting, bleeding especially from the stomach or intestine, dizziness, delirium, stroke and need for hospital admission (Taft et al . , Hartikainen et al . , Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, medication errors are ranked as the fourth to sixth cause of death in the USA (Hajjar et al 2007). In addition, the olderthose over 65 years of ageare at high risk for medication-related problems (Gusdal et al 2011, Olaniyan et al 2014, such as problems with nutrition, risk of falls or fall-related injuries, nausea and vomiting, bleeding especially from the stomach or intestine, dizziness, delirium, stroke and need for hospital admission (Taft et al 2005, Hartikainen et al 2007, Zhang et al 2007, Heuberger 2012, Davies & O'Mahony 2015.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study revealed that an acute exacerbation of chronic disease is the most common reason for an unplanned hospitalization or ED visit, which can be prevented through knowledge of risk factors, provider communication, and careful monitoring [29]. Other risk factors are polypharmacy [30], the length of HHC episode [31], worsening primary or secondary diagnosis or the development of a new problem [32], falls [30], and advancing age [30]. Strategies recommended for preventing hospitalization or ED visit are patient/caregiver education, 24-hour on-call nursing coverage, telehealth, management support, case management, front loading visits, medication management, fall prevention program, and positive physician and hospital relationships [33].…”
Section: Discussionmentioning
confidence: 99%
“…Agency policy/procedures associated with outcomes include: effective use of information technology or continuous quality improvement use, agency culture, use of action plans; and telemonitoring, staff education/training, and discharge planning (Burt & Pabin, 2006;Shaugnessy et al, 2002;Crossen-Sills, Toomey, & Doherty, 2006;Taft, 2005). Outcomes also differed depending on the type of payment (Shaughnessy, Schlenker, & Hittle, 1994).…”
Section: Downloaded By [Mcmaster University] At 01:42 27 December 2014mentioning
confidence: 99%